The law of contract, 1670-1870 / Warren Swain. - Swain, Warren, 1973- (Cambridge studies in English legal history., 2015)
The foundations for modern contract law were laid between 1670 and 1870. Rather than advancing a purely chronological account, this examination of the development of contract law doctrine in England during that time explores key themes in order to better understand the drivers of legal change. These themes include the relationship between lawyers and merchants, the role of equity, the place of statute, and the part played by legal literature. Developments are considered in the context of the legal system of the time and through those who were involved in litigation as lawyers, judges, jurors or litigants. It concludes that the way in which contract law developed was complex. Legal change was often uneven and slow, and some of the apparent changes had deep roots in the past. Clashes between conservative and more reformist tendencies were not uncommon.